2019
DOI: 10.1136/bmjopen-2019-031197
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental disorders among term infants exposed to antenatal corticosteroids during pregnancy: a population-based study

Abstract: ObjectiveAn increasing proportion of fetuses are exposed to antenatal corticosteroids (ACS). Despite their immediate beneficial effects, the long-term safety of ACS has been an ongoing source of concern. In the current study, we assessed the likelihood of neurodevelopmental problems among term infants exposed to ACS earlier in pregnancy compared with non-exposed term infants.DesignRetrospective cohort study (2006–2011). Median duration of follow-up was 7.8 (IQR 6.4–9.2) years.SettingPopulation-based study, Ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 63 publications
(76 reference statements)
2
56
0
3
Order By: Relevance
“…Corticosteroids should therefore not be used in asymptomatic SARS-CoV-2-positive patients or those with mild COVID-19 symptoms, unless preterm birth <34 + 0 weeks’ gestation is anticipated [2, 24]. Their use in ICU patients should be judiciously evaluated, as well as in patients at >34 + 0 weeks’ gestation [25].…”
Section: Antenatal Care For Women With Sars-cov-2 Infectionmentioning
confidence: 99%
“…Corticosteroids should therefore not be used in asymptomatic SARS-CoV-2-positive patients or those with mild COVID-19 symptoms, unless preterm birth <34 + 0 weeks’ gestation is anticipated [2, 24]. Their use in ICU patients should be judiciously evaluated, as well as in patients at >34 + 0 weeks’ gestation [25].…”
Section: Antenatal Care For Women With Sars-cov-2 Infectionmentioning
confidence: 99%
“…Questions remain about the balance between the risks and benefits of ACS after 34 + 6 weeks of gestation as there are no data on long-term outcomes. There are also increasing concerns about the long-term outcomes for babies exposed to ACS before 34 + 6 weeks of gestation but subsequently delivered at term [ 4 , 5 ]. This more recent evidence reveals new unknowns about ACS, only some of which are currently being actively investigated.…”
mentioning
confidence: 99%
“…Combined with the current low threshold for ACS administration, this means that a large number of babies exposed to ACS before 34 + 6 weeks of gestation may not actually benefit from the intervention. There is increasing concern about the potential for harm in such babies [ 4 , 5 ]. A Finnish observational register-based study found that ACS exposure was associated with a reduction in birth weight, birth length and head circumference in babies subsequently born at pre-term, early-term and term gestations [ 4 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations